The Hubungan Dompet Digital terhadap Peningkatan Perilaku Konsumtif Mahasiswa Universitas X di Kota Bandung - Azzahra, Keyzha; Aulia, Rahma Nurul (Asosiasi Ahli Administrasi Indonesia, 2024)
The purpose of the study was to analyze the influence e-wallet has on student consumptive behaviour. This research was conducted at X University in Bandung with 99 respondents from various study programs. The method used is descriptive quantitative, with data collected through questionnaires using G-form media distributed to active students who have used or often use e-wallets. Analyzed the data with a simple regression method to determine the level of influence using software SPSS and Smart PLS. The results revealed that the use of e-wallets with elements related to self-efficacy, trust, benefits, and ease of use has a significant positive impact of 82.2% on consumptive behaviour. However, there are other factors outside of this research model that affect 17.8%, assuming that peer pressure, lifestyle, and social environment are additional indications that affect consumptive behaviour. These findings not only help students become wiser in using e-wallets and avoid excessive consumption patterns, but also encourage universities to organize financial literacy programs. In addition, these findings also provide insight for e-wallet service providers to design more responsible promotions and support the use of e-wallets for important needs such as education and investment.